EFFECTS OF A TRADITIONAL CHINESE MEDICINE BASED DESENSITIZING GEL ON DENTIN HYPERSENSITIVITY - Wang, Hui; Zhao, Xiao; Ji, Ping (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background and Objective: Bamboo salt, Calcined oyster, Drynaria fortunei, Indigo naturalis and Rehmannia glutinosa have been the main ingredients of many formulations in Chinese medicine for the treatment of toothache. This study evaluated the effect of a new desensitizing gel on dentin hypersensitivity (DH). Materials and Methods: The desensitizing gel was prepared through a confirmed prescription of ingredients mentioned above and Poloxamer 407 (P407). The best concentration of P407 in prescription was screened according to the gelatin temperature of gel. Scanning electron microscopy (SEM) was used to evaluate the dentinal tubule occlusion of 32 human premolars under various treatments including the desensitizing gel. Randomized controlled clinical trials were conducted to evaluate the clinical effect of the desensitizing gel. Results: The best concentration of P407 in prescription was 0.30g/ml. Scanning electron micrographs of the cross-sectional and longitudinal dentin surfaces revealed most of the dentinal tubules were occluded by sedimentation after desensitizing gel treatment, and significant difference existed compared to the control groups. Randomized clinical trials showed 173.72% and 270.07% mean relative improvements on tactile hypersensitivity at one-month and two-month follow-ups, and 54.11% and 90.91% mean relative reductions on air blast hypersensitivity at one-month and two-month follow-ups (p<0.05). There was no statistical difference between the desensitizing gel and Duraphat group at different time intervals (p>0.05). Conclusions: Based on these findings, the desensitizing gel exhibits an obvious effect on dentinal tubule occlusion. Besides, data of the randomized clinical trials indicate a potential role for the desensitizing gel in managing DH.